ADVANCING CROP PRODUCTION SYSTEMS: INTEGRATING SUPERIOR VARIETIES AND PRECISION AGRICULTURE FOR SUSTAINABLE YIELD ENHANCEMENT - Pramono Hadi; Marco Ferrari; Lucia Romano (Yayasan Adra Karima Hubbi, 2026)
Global food demand continues to rise due to population growth, climate variability, and changing consumption patterns, placing increasing pressure on agricultural production systems. Conventional farming practices often struggle to achieve sustainable yield improvement while maintaining resource efficiency and environmental integrity. The integration of superior crop varieties with precision agriculture technologies has emerged as a promising strategy to enhance productivity, optimize input use, and promote sustainable agricultural development. This study aims to evaluate the effectiveness of integrating high-performing crop varieties with precision agriculture approaches in improving crop yield, resource efficiency, and production sustainability. The research focuses on identifying synergistic effects between genetic improvement and site-specific management practices in modern crop production systems. A mixed-methods approach was employed, combining field experiments, secondary agronomic data analysis, and precision farming measurements. Superior crop varieties were assessed under precision-managed conditions using variable-rate fertilization, sensor-based monitoring, and data-driven decision support systems. Yield performance, input efficiency, and environmental indicators were analyzed using descriptive statistics and comparative analysis. Results demonstrate that the combined application of superior varieties and precision agriculture significantly increased crop yields while reducing fertilizer and water inputs. Improved nutrient-use efficiency and yield stability were observed across different growing conditions. The study concludes that integrating genetic advancement with precision agriculture offers a viable pathway for sustainable yield enhancement. This approach supports resilient, efficient, and environmentally responsible crop production systems.